An examination of the burnout levels of healthcare professionals according to some variables during the COVID-19 pandemic - Okray, Zihniye; Bilgi Abatay, Güley (The European Research Journal, 2023)
Objectives: The objective of this study is to examine the effects on burnout levels of socio-demographic characteristics of healthcare professionals in different professions who are on active duty during the COVID-19 pandemic. Methods: Obtained through socio-demographic information form created by the researchers and Maslach Burnout Scale (MBS) e-data collection method. Results: It has been found out that gender variable reveals important differences among healthcare professionals and female healthcare professionals are more exhausted than men, the burnout levels of healthcare professionals who have a one-to-one relationship with COVID-19 patients are higher, and healthcare professionals trying to obtain information about the pandemic through social media are more exhausted than others. Variables such as marital status, education level, and being diagnosed with COVID-19 were not found to affect burnout in this study. However, when the data set was divided into two over the gender variable, it was observed that the education level variable affected emotional exhaustion scores among female participants. Although the emotional exhaustion scores of female participants with doctoral and high school education did not reveal a significant difference between the groups in the advanced statistical study, they revealed a significant difference according to the One-Way Analysis of Variance. The group with the highest burnout among healthcare professionals was determined as nurses. Conclusions: It is important to carry out studies on psychological support and coping with burnout for healthcare professionals who are on active duty during the pandemic.